2008 46th Annual Allerton Conference on Communication, Control, and Computing 2008
DOI: 10.1109/allerton.2008.4797542
|View full text |Cite
|
Sign up to set email alerts
|

Diversity multiplexing tradeoff of asynchronous cooperative relay networks

Abstract: The assumption of nodes in a cooperative communication relay network operating in synchronous fashion is often unrealistic. In the present paper we consider two different models of asynchronous operation in cooperativediversity networks experiencing slow fading and examine the corresponding diversity-multiplexing tradeoffs (DMT). For both models, we propose protocols and distributed space-time codes that asymptotically achieve the transmit diversity bound for all multiplexing gains and for number of relays N ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…In this line of thought, the author of [6] derived the diversity-multiplexing tradeoff curve of two asynchronous cooperative diversity schemes and showed that they achieve the same performance as the synchronous Space-Time coded scheme. In [11], the authors considered two different models of asynchronous cooperative relay networks and propose a variant of the Slotted Amplify and Forward (SAF) protocol which asymptotically achieves the transmit diversity bound for both these models.…”
Section: Introductionmentioning
confidence: 99%
“…In this line of thought, the author of [6] derived the diversity-multiplexing tradeoff curve of two asynchronous cooperative diversity schemes and showed that they achieve the same performance as the synchronous Space-Time coded scheme. In [11], the authors considered two different models of asynchronous cooperative relay networks and propose a variant of the Slotted Amplify and Forward (SAF) protocol which asymptotically achieves the transmit diversity bound for both these models.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the same DMT performance as that of the corresponding synchronous network is achieved. In [19], under the assumption of having integer delays, two different models of asynchronism in a cooperative relay network with at least two relays are considered. For each model, a variant of the slotted amplify-and-forward (SAF) relaying protocol [20] is proposed which asymptotically achieves the transmit diversity bound in the absence of a direct source-destination link.…”
Section: Introductionmentioning
confidence: 99%
“…For each model, a variant of the slotted amplify-and-forward (SAF) relaying protocol [20] is proposed which asymptotically achieves the transmit diversity bound in the absence of a direct source-destination link. In the presence of this link, it is shown in [21] that the SAF protocol is asymptotically optimal under both models of asynchronism. It is worth nothing that in the SAF protocol, the relays are assumed to be isolated from each other which is in fact often unrealistic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation